EFEKTIVITAS METODE PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI KELAS X SMA SWASTA BINA ARTHA - Devi Lestari; Nunik Ardiana; Roslian Lubis (JURNAL MathEdu (Mathematic Education Journal), 2020)
Abstract This research aims to see: 1) How the model of learning effectiveness Numbered Head Together (NHT) in class X SMA private Bina Artha, 2) How is the overview of the ability to solve students ' mathematical problems in SPLDV materials ( Two-variable Linear equation system) before and after application of learning model in class X SMA private Bina Artha, 3) is NHT Learning model is effective against student mathematical problem solving ability in class X private SMA Bina Artha. This research was conducted using experimental methods. The research was conducted at the Bina Artha Private high School. The population used by all students of grade X SMA Sasta Bina Artha amounted to 107 students. The sampling technique is done by a cluserter random sampling technique. The samples in this study were the X IPA2 class of 36 students. The data collection methods used are RPP, observation, and test. The average value of use of NHT models in SPLDV material (two variable Linear equation system) was score 13.85 "very good" category. While the results of learning students in SPLDV material before using NHT learning model obtained average value 68.67 category "Good" and after the use of learning model NHT obtained average value 72.36 "very good" category. Then the data analysis technique used is Test T. The analysis of the hypothesis testing is processed using SPSS. From the results of the analysis of the hypothesis test, obtained the pretests value of the tcount of 41.22 while the posttest tcount value of 43.70. Based on the results above, it can be concluded that a significant value of sig (2-tailed smaller than the value (0.000 < 0.05) is obtained. This suggests that hypotheses submitted in this study may be accepted or approved. This means that there is a significant influence simultaneously before and after the use of the learning model Numbered Head Together (NHT) on the ability to problem solving students mathematics in class X private SMA Bina Artha. Keywords: Numbered Head Together Solving Ability, Mathematically